PEMANFAATAN RPO (RED PALM OIL) SEBAGAI SUMBER PROVITAMIN A ALAMI PADA PRODUK MI INSTAN UNTUK ANAK BALITA - Sri Anna Marliyati; Hardinsyah Hardinsyah; Neysa Rucita (Food and Nutrition Society of Indonesia, 2010)
The objective of this research was to study the use of RPO as a sources of natural provitamin A in instant noodle product for under five children. For this purpose 5 formulas were developed based on RPO’s level added to the formula (0%, 25%, 50%, 75% and 100%). The result shown that instant noodle with 75% RPO was the best formula of RPO instant noodle. No significant difference in acceptance between this formula and other commercial instant noodle (α>0.05). The result of RPO instant noodle’s chemical analysis were moisture content 7.40% (wb), ash content 2.51% (db), protein content 13.66% (db), fat content 9.84% (db), carbohydrate was 74.49% (db) and carotenoid 136.41 ppm (≈ 76.42 ppm β-carotene ≈ 636.8 RE/serving size). RPO instant noodle has physical properties as follow, optimum cooking time was 3 minutes, the color was yellow-red, elasticity properties was 261.94%-455.65% and water holding capacity was 137.98%. This noodle was contributing 100% of vitamin A RDA for the children.